Study on the skid resistance performance of wet and slippery asphalt pavement on curved roads in aeolian sand areas - Qiang Pan; Ping Li; Xiaoyan Liu; Jingsheng Pan (PLoS ONE, 2025)
In order to study the change law of the anti sliding performance of desert highway in the wet and slippery state of the curve, two different curves and straight roads of the same highway were selected for the field test through the method of field test. The British pencil number (BPN) and mean texture depth (MTD) were selected as the evaluation indexes, and the change law of BPN and MTD at different curves and straight roads with the amount of sand and water was measured. In order to clarify the sensitivity of the anti sliding performance under different humidity, the water volume (humidity) that has the greatest impact on BPN and MTD was obtained by using grey correlation analysis, and then the anti sliding performance at the curves and straight roads was evaluated.The performance is compared and analyzed. The results show that the anti sliding performance of the curve and the straight road decreased by 33.3% and 32.0%, respectively, and the change law of the two is basically the same. The water aggravates the decline of the anti sliding performance of the road surface, and the anti sliding performance of the curve at low speed is about 3.2% less than that of the straight road.